Microglia Activation and Recruitment of Circulating Macrophages During Ischemic Experimental Branch Retinal Vein Occlusion - Andreas Ebneter; Despina Kokona; Nadia Schneider; Martin S. Zinkernagel (2017)
Purpose: To characterize retinal microglia activation and macrophage recruitment in experimental branch retinal vein occlusion (BRVO). Methods: Experimental BRVO was induced in Balb/c mice and histologic changes were studied. Tissue hypoxia was visualized using pimonidazole hydrochloride. Monocyte-derived retinal cells were quantified using histology and flow cytometry. To investigate the dynamics of invading blood-borne macrophages, chimera mice were generated using bone marrow grafts from Cx3cr1(gfp/gfp) mice to rescue lethally irradiated wild-type BALB/c mice. Longitudinal in vivo imaging was performed to monitor cell invasion. The levels of proinflammatory cytokines in the retina were quantified by quantitative real-time PCR. Results: Histology showed disruption of tissue architecture and temporary swelling with marked hypoxia coinciding with increased VEGF-A and hypoxia inducible factor-1α (HIF-1α) expression and elevation of proinflammatory cytokines within 3 days after experimental BRVO, followed by thinning of the inner retinal layers at later time points. Proinflammatory cytokine levels were elevated. Activation of resident retinal microglia and recruitment of circulating macrophages in areas of hypoxic retina were evident early after the insult and peaked at day 7, remaining elevated for up to 28 days. Flow cytometry showed upregulation of CD68 and major histocompatibility complex class-II (MHC-II) expression at day 3, culminating at day 7. Conclusions: Experimental BRVO causes hypoxia and breakdown of the inner blood–retina barrier, followed by activation of microglia and invasion of macrophages from the systemic circulation. Consequently, treatments targeting microglia activation or macrophage recruitment might potentially mitigate the sequelae and attenuate degenerative changes induced by retinal vein occlusion.